Diagn Interv Radiol 2022
DOI: 10.5152/dir.2022.221881
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia: lessons learned, challenges, and preparing for the future

Abstract: Coronavirus disease 2019 (COVID-19) is a viral disease that causes life-threatening health problems during acute illness, causing a pandemic and millions of deaths. Although computed tomography (CT) was used as a diagnostic tool for COVID-19 in the early period of the pandemic due to the inaccessibility or long duration of the polymerase chain reaction tests, current studies have revealed that CT scan should not be used to diagnose COVID-19. However, radiologic findings are vital in assessing pneumonia severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 75 publications
0
5
0
2
Order By: Relevance
“…Some studies have suggested that these findings would gradually resolve over time, but others have reported persistent septal thickening even after many years. [16][17][18] Han and colleagues 9 reported that some participants had unchanging GGOs and reticular abnormalities in a 2-year follow-up prospective study. Another study found that half of the subpleural GGOs detected on CT scans in post-COVID-19 patients contained bronchiolectasis, which could indicate irreversible interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that these findings would gradually resolve over time, but others have reported persistent septal thickening even after many years. [16][17][18] Han and colleagues 9 reported that some participants had unchanging GGOs and reticular abnormalities in a 2-year follow-up prospective study. Another study found that half of the subpleural GGOs detected on CT scans in post-COVID-19 patients contained bronchiolectasis, which could indicate irreversible interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ground-glass opacities are nonfibrotic interstitial lung abnormalities, whereas reticular abnormalities are considered fibrotic findings, both of which have been observed on CT scans in patients with a history of COVID-19. Some studies have suggested that these findings would gradually resolve over time, but others have reported persistent septal thickening even after many years 16–18 . Han and colleagues 9 reported that some participants had unchanging GGOs and reticular abnormalities in a 2-year follow-up prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…With its emergence, the pandemic of the disease COVID-19, caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), caused a significant increase in the number of hospitalizations and deaths, primarily due to pneumonia with multiorgan involvement [1,2,3,4]. More and more vaccines against COVID-19 and new treatments are being developed worldwide [5,6,7,8].…”
Section: Connection Of the Publication With Planned Research Workmentioning
confidence: 99%
“…Зі своєю появою пандемія захворювання COVID-19, викликаного новим коронавірусом 2 важкого гострого респіраторного синдрому (SARS-CoV-2), спричинила значне збільшення кількості випадків госпіталізацій та смертей, зумовлених насамперед пневмонією з поліорганним ураженням [1,2,3,4]. У всьому світі розробляється все більше вакцин проти COVID-19 та нових методів лікування [5,6,7,8].…”
Section: клінічна характеристика пацієнтів з тяжким та критичним пере...unclassified
See 1 more Smart Citation